Islamophobia Epistemic Racism Perspective - Ryan Arief Rahman; Ahmad Zulhaq (al-Afkar, Journal For Islamic Studies, 2024)
Islamophobic discourse has been a global phenomenon that has harmed Islam since the early 20th century. This article aims to reveal the root causes of Islamophobia with the perspective of epistemic racism initiated by Ramón Grosfoguel in sociological discourse. The material object of this study is Islamophobia found in Western literature and studies, which is explored using the theory of epistemic racism as a formal object. The results of this study reveal that epistemic racism towards the West manifests itself in two attitudes: first, political-identity hegemony formed from epistemic privilege and Eurocentrism. Second, othering (Fanaticism and Unilateral Claims of Truth) with superiority that considers non-Western inferior and backward. These two attitudes produce wrong knowledge of non-Westerners, especially Islam. Ultimately it has implications for hatred and dislike of Islam. This is in line with what S said. M. N. Al-Attas that Western knowledge about Islam is not complete (corruption of knowledge). This article concludes that Islamophobia is an attitude that Ramon Grosfoguel considers to be an act equivalent to racism that hates a certain race, but in this case it is a racist attitude between followers of a certain religion.